(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2021)
This scientific paper discusses the features of one of the most common legal obligations – the transfer of property (dare). It is regulated in all legislations throughout the world. The subject of research envelops its peculiarities, according to the two major continental families – the Roman and the German, compared with those of the Anglo-Saxon legal system. Some distinctions of the obligation to transfer property under Bulgarian law, which manifest deviations from its reception via French through Italian law, have been thoroughly reviewed.